Examining internships as a high-impact educational practice - Keller, Kerri Day (Kansas State University, 2012)
Colleges and universities across the United States seek new, creative, and impactful ways to enhance student engagement. The study of student engagement has led to the identification of several “high-impact” educational practices that appear to generate higher levels of student performance, learning, and development than the traditional classroom experience (Brownell & Swaner, 2010). Internships – when done well – are among the recommended high-impact educational practices (Kuh, 2008). This qualitative study investigated internships to address the following research questions: What is the essence of internships that are done well? What are the student learning outcomes of internships that are done well? Utilizing interviews and a phenomenological approach, this study reconstructed internship experiences of 19 undergraduate students. For the triangulation of data collection, 5 faculty members and 5 employer representatives were also interviewed about their observations regarding student internships. After open coding and analyzing interview transcripts, four essence themes and four outcome themes emerged from the data. According to study participants, internships that are done well require commitment, connect the classroom to career, facilitate good communication, and provide a sense of community. In regards to resulting outcomes, internships that are done well develop the competencies of students, produce career-related crystallization, build self-confidence, and generate capital. The results suggest that when internships are done well, they can embody Kuh’s (2008) six elements of high impact practices as they are effortful, include feedback, apply learning, prompt reflection, build relationships, and engage across differences. The findings of this study have the potential to assist the campus community – faculty, advisors, and career development professionals – as they help students fulfill their learning and career development goals (O’Neill, 2010). First, this study’s findings essentially point to the need for students to demonstrate initiative and fundamental skills during internships. Second, employers must continue to be informed about what constitutes a meaningful internship experience for students. Third, universities should “scale up” high-impact educational practices like internships (Brownell & Swaner, 2010) by creating a developmental approach for program implementation. Furthermore, everyone in the campus community must work together to effectively facilitate internships and other high-impact educational practices.
Keywords: High-impact; Internship; Career; College students; Student engagement; Higher education; Higher Education (0745)